Program Tempel Nadzam Bergilir untuk Mempermudah Santri Menghafal Nadzam Maqsud, Imriti, dan Alfiyah di Pondok Pesantren At-Taroqqi Karongan Sampang - Ach. Fatoni; Nelud Darajatul Aliyah (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
The Rotating Nadzam Paste Program is a learning innovation at the At-Taroqqi Karongan Sampang Islamic Boarding School which aims to make it easier for students to memorize the Maqsud, Imriti, and Alfiyah nadzams. In this program, the nadzams to be memorized are attached to various strategic places around the boarding school in rotation, so that students can easily access and repeat their memorization at any time. This method is designed to create a more interactive and contextual learning atmosphere, with the hope of improving students' memory and understanding of the nadzams being studied. This study aims to analyze the effectiveness of the rotating nadzam paste program in helping students memorize quickly and accurately, as well as to identify the obstacles and supporting factors that influence the success of this program. It is hoped that this program can provide solutions to the challenges of memorizing nadzams in Islamic boarding schools